Materials science aspects of the production of wooden utensils of Bronze and Early Iron Ages from the North Black Sea and North Azov Sea regions - Kateryna Minakova; Maryna Serheieva (Cхід, 2017)
The article presents the results of analysis of nine wooden utensils of the Bronze and Early Iron Ages (Catacomb, Zrubna and Sciphian cultures) in comparison with previous analysis of different authors. In eight cases remains were represented by deciduous trees (mostly maple - Acer sp.). Comparison of this results with data from other investigators allowed to conclude that for making objects from wood used mainly local breeds. When selecting trees for making utensils, old masters have used certain principles such as ease of cutting and aesthetic preferences. For the manufacture of wooden utensils, pastoral nomads used mostly local wood that grew in gullies and floodplains. Most often for the manufacture of wooden utensils used maple, which is recorded in the Catacomb monuments, Zrubna, Scythian and Sarmatian burials. The generally accepted view is of the greatest accessibility of oak as a material for the manufacture of wooden utensils. However, our analysis and findings of other studies suggest limited use of wood for making utensils. Only in one case, for making fixed tray was used oak bark. However, generally we have to assume that the old masters avoided the use of oak wood for cutting wooden utensils due to its physical properties and considering that the tools were quite simple for working with brittle kinds of wood. In two cases (burial 17 and 23 of Vysoka Mohyla Zaporizhzhya oblast) the data shows that for producing of the bowl chestnut wood (Castanea sp.) was utilized. In the Steppe zone the willow and birch bark were broadly widespread. They could be used to make baskets and birch products, however, we do not have the results of relevant analyzes to talk about it with confidence.